The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12872-019-1174-4
|View full text |Cite
|
Sign up to set email alerts
|

Swallow syncope: a case report and review of literature

Abstract: Background Swallow or deglutition syncope is an unusual type of neurally-mediated syncope associated with life-threatening bradyarrhythmia and hypotension. It is a difficult condition to diagnose with commonly delayed diagnosis and management. There is lack of review articles that elucidate the basic demographics, clinical characteristics and management of this rare condition. This publication systematically reviews the 101 case reports published since 1793 on swallow syncope. Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 82 publications
1
47
0
Order By: Relevance
“…This is believed to be due to afferent impulses from the esophageal plexus which travel via the vagus nerve to the brain stem and then trigger efferent fibers to signal back through the vagus nerve to the heart. This type of syncope has been reported since 1793 by Spens, but literature review has not shown syncope to occur in achalasia without swallowing [2]. We present the case of a patient with achalasia and a nonswallowing syncopal episode.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is believed to be due to afferent impulses from the esophageal plexus which travel via the vagus nerve to the brain stem and then trigger efferent fibers to signal back through the vagus nerve to the heart. This type of syncope has been reported since 1793 by Spens, but literature review has not shown syncope to occur in achalasia without swallowing [2]. We present the case of a patient with achalasia and a nonswallowing syncopal episode.…”
Section: Introductionmentioning
confidence: 75%
“…This is all thought to be due to reflex arcs in the parasympathetic system between afferent and efferent fibers [3]. Dilatational treatment of the achalasia typically results in complete resolution of the deglutition syncope [2,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…DS is often found in older adults, with a mean reported age of 57.5 years at the time of initial presentation [13]. The exact mechanism of DS remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to diagnosing DS, it is essential to rule out any esophageal disorders and cardiac diseases beforehand [9]. The diagnosis of DS involves careful history taking and recognition of presyncopal events or syncope triggered by the process of swallowing (provocative test) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The nature and severity of CI differs between types of reflex syncope. In swallow syncope asystole due to an AV-block has been frequently described (8), although a selection bias cannot be ruled out. This "reflex AV-block" differs in some respects from an intrinsic AV-block, and is probably due to stronger inhibition of the AV-than the SA-node.…”
Section: And Vd In Reflex Syncopementioning
confidence: 99%